2020
DOI: 10.2139/ssrn.3632058
|View full text |Cite
|
Sign up to set email alerts
|

Cross-Sectional Inquiry on Employability and Employment Status of Bachelor of Secondary Education Graduates (2016-2018): A Tracer Study

Abstract: Higher education institutions are expected to produce quality and competitive graduates for the job market and nation-building. In realizing this role, the Bukidnon State University needs to ensure that graduates may land a job-relevant and aligned with their education and training. With this, a tracer study was conducted to verify whether the three batches of graduates are employed and are employable. It ascertained their employability based on their work experience from graduation to the present job. It empl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
6
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(10 citation statements)
references
References 10 publications
3
6
1
Order By: Relevance
“…Noticeably, the employment to teachingrelated works has decreased to 56.3 percent. These results are lower than the previous tracer conducted, wherein 89 percent of the 2018 graduates, and 81 percent of 2016 graduates had been employed to teaching-related jobs (Caingcoy et al, 2020).…”
Section: Employment Statuscontrasting
confidence: 67%
See 2 more Smart Citations
“…Noticeably, the employment to teachingrelated works has decreased to 56.3 percent. These results are lower than the previous tracer conducted, wherein 89 percent of the 2018 graduates, and 81 percent of 2016 graduates had been employed to teaching-related jobs (Caingcoy et al, 2020).…”
Section: Employment Statuscontrasting
confidence: 67%
“…Time does matter in obtaining a permanent job tenure. This reality was shown also in previous batches covered in previous tracer wherein only 60 and 40 percent of the 2016 and 2017 graduates, respectively, had permanent status in their employment (Caingcoy et al, 2020). This scenario was recorded after two or three years from graduation period.…”
Section: Figure 3 Employment Status Of 2019 Bse Graduatessupporting
confidence: 57%
See 1 more Smart Citation
“…Several teacher education institutions in the Philippines conducted Graduate Tracer Studies (GTS) to track and profile their Bachelor in Elementary Education (BEED) and Bachelor of Secondary Education (BSED) graduates (Abas et al, 2020;Abela et al, 2015;Aclan et al, 2018;Almejas et al, 2017;Antiojo, 2018;Aquino et al, 2015;Bihag-boholano, 2012;Caingcoy & Barroso, 2020;Cañizares, 2015;Cornillez et al, 2021;Daguplo et al, 2019;Gines, 2014;Oboza, 2017;Rojas & Rojas, 2016;Reusia et al, 2020;Tutor et al, 2019;Ulanday, 2021). Abas et al (2020) showed that the majority of the graduates are hired, notwithstanding the various competencies gained throughout their college years.…”
Section: Related Studiesmentioning
confidence: 99%
“…Assuring quality graduates has presented a challenge for higher education institutions (HEIs) offering teacher education programs in providing relevant teacher training and preparation to meet the demands of a growing society and challenging times (Aquino et al, 2015;Daguplo et al, 2019;Coman et al, 2020;Pentang et al, 2021). It is the responsibility of HEIs to produce quality and competitive graduates (Abela et al, 2020;Caingcoy & Barroso, 2020) and to ensure that they are employed (Abas et al, 2020;Aclan et al, 2018). Higher education is valued based on its capacity to give possibilities for graduates seeking future employment and creating a strong professional path (Ali & Jalal, 2018;Rojas & Rojas, 2016) since one can only obtain a successful career if they have obtained appropriate education and training (Bihag-boholano, 2012;Ulanday, 2021).…”
Section: Introductionmentioning
confidence: 99%